Synthesis and Characterization of PANI/PEANI Conducting Polymers-Au/Ag Nanoparticle Composites - Vohra, Sujata (My University, 2014)
The mixing of polymer and nanoscale inorganic particles has been recognized as a potential and economic method of producing new materials with better mechanical, electrical, optical and electrochemical behaviour and also with new functions. The present work reports the synthesis of such materials with reference to PANI & PEANI as conducting polymers and gold and silver as metal nanoparticles. The thesis describes synthesis of gold and silver nanoparticles by various methods and their characterisation for morphological, structural & optical properties. Gold nanoparticles were synthesised using different reducing and capping agents. These reagents and their respective ratios helped in controlling size, shape and distribution of nanoparticles. Silver nanoparticles (AgNPs) were synthesised by reducing silver ions using NaBH4/ethylene glycol (reducing agents) in presence of PVP (capping agent). The size of AgNPs was less than 10 nm or more than 10 nm depending upon the reduction time and temperature. The thin films of PANI and its composites were synthesised by spin coating method. The composites exhibited higher conductivity than PANI. It has been possible to cast the thin film of this material on ITO surface, which may find applications in switching devices, semiconductors and sensors. In another study, nanocomposites of PANI/AgCl were synthesised by chemical polymerisation/precipitation in aqueous HCl solution using both aniline monomer and AgNO3 precursors in different molar ratios in PVP. The composite possesses improved stability than individual constituents, as PVP capped AgCl nanoparticles are acting nanofillers within polymer chains showing higher compactness in the polymer matrix. A new class of conducting polymer i.e. poly (2-ethylaniline) was prepared by oxidative polymerisation of 2-ethylaniline with different dopant acids (sulphuric acid, o-phosphoric acid, p-toluene sulphonic acid, hydrochloric acid). PEANI/Ag nanocomposites (using PTSA, SA, and PA dopant acid) and PEANI/Au nanocomposite (with PTSA as dopant acid) were prepared via in situ chemical synthesis route (simultaneous polymerisation and precipitation). From the I-V studies, it was found that conductivity decreased on addition of metal nanoparticles. The nanoparticles may have acted as catalyst as well as filler in the process of polymerisation. The formation of PEANI/metal composites also influences the polymer thermal properties as the oxidation state increased. In short, it is concluded that the results of synthesising the above said nanoparticles and nanocomposites suggest that they could be useful for several applications like semiconductor devices, coating, catalysis and many more with lot of scope in future study.
PHD, SCBC
Keywords: polyaniline; polyethylaniline; nanocomposites; conducting polymers